A controlled trial of reduced meal frequency without caloric restriction in healthy, normal-weight, middle-aged adults - Stote, Kim S; Baer, David J; Spears, Karen; Paul, David R; Harris, G Keith; Rumpler, William V; Strycula, Pilar; Najjar, Samer S; Ferrucci, Luigi; Ingram, Donald K; Longo, Dan L; Mattson, Mark P (The American journal of clinical nutrition, 2007)
Although consumption of 3 meals/d is the most common pattern of eating in industrialized countries, a scientific rationale for this meal frequency with respect to optimal health is lacking. A diet with less meal frequency can improve the health and extend the lifespan of laboratory animals, but its effect on humans has never been tested. A pilot study was conducted to establish the effects of a reduced-meal-frequency diet on health indicators in healthy, normal-weight adults. The study was a randomized crossover design with two 8-wk treatment periods. During the treatment periods, subjects consumed all of the calories needed for weight maintenance in either 3 meals/d or 1 meal/d. Subjects who completed the study maintained their body weight within 2 kg of their initial weight throughout the 6-mo period. There were no significant effects of meal frequency on heart rate, body temperature, or most of the blood variables measured. However, when consuming 1 meal/d, subjects had a significant increase in hunger; a significant modification of body composition, including reductions in fat mass; significant increases in blood pressure and in total, LDL-, and HDL-cholesterol concentrations; and a significant decrease in concentrations of cortisol. Normal-weight subjects are able to comply with a 1 meal/d diet. When meal frequency is decreased without a reduction in overall calorie intake, modest changes occur in body composition, some cardiovascular disease risk factors, and hematologic variables. Diurnal variations may affect outcomes.